Development of Coffee Products Based on Local Wisdom As an International Culinary Tourism Attraction - Putri Bulan Bumi Aji; Ervilia Dwi Nanda P; Adien Husnun Nabila; Rindu Rika Gamayuni (Indonesian Journal of Community Engagement, 2025)
Indonesia is one of the largest coffee producing countries in the world, which has various coffee varieties.  According to data from the Central Statistics Agency, Indonesia 2021 produces two main coffee varieties, Arabica and Robusta, making it the fourth largest coffee producer in the world. This diversity represents great potential for the development of coffee products based on local wisdom and can become an attraction for international culinary tourism. One of the coffee products that we will promote or present in this activity is Robusta coffee, namely Original Bahalways Coffee from West Lampung Regency, which has a distinctive Original taste. The aim of this activity is to develop coffee products that not only use local raw materials but also incorporate local knowledge in processing and serving coffee. The methods in this activity are presentation and discussion. Based on the results of the activity, it can be concluded that the achievement of the coffee products produced can become an international gastronomic tourism attraction that shows the richness of Indonesian culture.